2007
DOI: 10.1007/s10792-005-4836-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of blindness and visual impairment among school children in south-western Nigeria

Abstract: The aim of the study was to assess the prevalence and identify the causes of blindness and visual impairment in school children of Ilesa-East Local Government Area of Osun State, Nigeria. A total of 1144 school children in primary and secondary schools were selected using a 2-stage random sampling method and examined to determine the prevalence and causes of blindness and visual impairment. A total of 17 (1.48%) children were blind or visually impaired. These comprised of 11 (0.96%) children who were visually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
37
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 6 publications
20
37
4
Order By: Relevance
“…This agrees with other hospital based studies as well as school eye health surveys that have also reported it as either the commonest [8,9,[14][15][16] or the second most common [2,7,10] cause of eye disease in children. Conjunctivitis was significantly higher in females (p=0.008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with other hospital based studies as well as school eye health surveys that have also reported it as either the commonest [8,9,[14][15][16] or the second most common [2,7,10] cause of eye disease in children. Conjunctivitis was significantly higher in females (p=0.008).…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with the previous clinical studies in Nigeria, which show that myopia is the most common refractive cause of visual impairment [3,5]. However, Ayanniyi et al [13,14] in a private optometry practice in AdoEkiti Nigeria and Bagaiya and Pam [16] in Kaduna State North Central Nigeria among University community both found hyperopia to be the commonest refractive error.…”
Section: Discussionsupporting
confidence: 88%
“…Others studies also observed Conjunctivitis as a leading cause of ocular morbidity. 12,20 Prevalence of Vitamin A deficiency observed 2.4% in present studies and similar observation made other studies also. 21,22 But high prevalence observed by Prajapati at al.…”
Section: Discussionsupporting
confidence: 91%
“…All pupils with significant refractive errors were myopic (Wedner & Foster, 2000). The results are consistent with the fi ndings elsewhere (Ajaiyeoba et al, 2007). In a previous study in north-western Tanzania a low (1.0%) prevalence of refractive error was reported (Wedner & Foster, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…In adults (>15 years) myopia rose to 19.3%, hyperopia fell to 9.8%, and astigmatism was detected in 12.9% (Dandona et al, 2002). Like in our study, a higher prevalence of ocular disorders in females than males has also been reported in Nigeria (Ajaiyeoba et al, 2006).…”
Section: Discussionsupporting
confidence: 87%